Effectiveness of Silver Nanoparticles Utilization from Microalgae Chlorella Pyrenoidosa and Dunaliella Salina for Vaname Shrimp Farming in the Muara Tami District of Jayapura - Imam Mishbach; Barnabas Bara'padang; Dirk Y. P. Runtuboi; Suharno Suharno; Puguh Sujarta; Liyatin Gea (Pusat Publikasi Nusantara, 2024)
Muara Tami district in Jayapura has significant potential for vaname shrimp farming. However, environmental problems and pathogens are often the main obstacles that reduce the productivity of this culture. One of the innovative solutions being developed to overcome these problems is the application of nanoparticle innovation in aquaculture, especially silver nanoparticles (AgNPs). This study aims to assess the effectiveness of using silver nanoparticles obtained from microalgae Chlorella pyrenoidosa and Dunaliella salina as an alternative that can support the development of vaname shrimp farming. The research method used a qualitative approach, with data collected through direct observation, involving the manufacture of silver nanoparticles from microalgae C. pyrenoidosa and D. salina, which were then used as feed for vaname shrimp. After observation, the data were processed and supported by related literature. The results showed that the application of silver nanoparticles from microalgae was effective on the growth and survival rate of cultured vaname shrimp in Muara Tami District. Thus, these findings indicate that microalgae have great potential as natural agents that can help reduce toxicity in aquaculture environments, creating healthier and more sustainable shrimp farming conditions.